A digital game for learning basic calculus: A concept paper - Yaacob, Nurul Aityqah; Mohamed, Nadiah; Ahmad, Mardiana; Wan Suhaimi, Wan Faizatul Syarlinny; Shareza, Syahirah; Abdul Halim, Rabiatul Adawiyah (2022)
The COVID-19 pandemic has caused many teachers around the world to abruptly switch from face-to-face to online teaching. Digital games can provide the context and environment in reinforcing the learning of basic calculus in class. The game strategy makes learning meaningful, varied and fun. This study is unique as it seeks to integrate appropriate elements of a digital game design with that of calculus education; thus, making learning fun, engaging and consequential. The purpose of this article is to discuss the feasibility of utilizing open distance learning to extend educational opportunities for pre-diploma students enrolled in institutions of higher education. This paper explores the benefits of using digital games to deliver an inclusive education to pre-diploma students and makes recommendations based on the findings of a literature research.